The naive picture and unbridled world in the story Lilika by Dragoslav Mihailović - Hamović, Valentina (Studia et Documenta Slavica, 2020)
This paper deals with the motifs of eroticism in the story Lilika by Dragoslav Mihailović, in the context of the growing up and maturing of the young ten-year-old heroine. The erotic in this story is brought down to the level of pornography – animal instincts in the scenes of the girl’s drunken mother and stepfather grabbing each other by the arms and legs in front of the child, slipping hands under the skirt, chasing each other with knives and pushing their tongues into each other’s mouth. They stretch the sphere of eroticism to extremes, which is, in this case, thanatically tainted. And such a bestial life that is led by the stepfather and the mother is not far from true violence over the ten-year-old girl, who is beaten and tied to a bed by the parents; and apart from the physical abuse, whose effects are frequent blood spots and bruises under Lilika’s eyes and uncontrolled night urination, there is an additional passive kind of violence towards the girl – ignoring and neglecting her. In a series of circumstances in which she finds herself unwillingly, there forms an inner framework of the heroine’s unhappy childhood, whose basic problem was posed already at her very birth, and it is the question of her identity.